PERAN TRANSFORMASI DIGITAL DALAM OPTIMALISASI TATA KELOLA LEMBAGA PENDIDIKAN BERBASIS KEAGAMAAN - Ahmad Fithonik Ibnu Malik; M. Ali Misbahul Anwar; Aji Wahyudin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
In the digital era, faith-based educational institutions face significant challenges in adapting to technological advancements to enhance governance and educational quality. Although digital transformation has become increasingly vital in the educational landscape, the digital divide remains a major concern, particularly among madrasahs and pesantrens (Islamic boarding schools) in Indonesia.This study explores the role of digital technology in improving the efficiency of governance and operations within faith-based educational institutions. Employing a qualitative case study approach, data were collected through direct observation, in-depth interviews with key stakeholders, and the analysis of official documents and academic literature.The findings indicate that the implementation of digital systems such as Learning Management Systems (LMS), cloud-based platforms, and financial information systems has significantly enhanced transparency, accountability, and academic monitoring. Nevertheless, several obstacles persist, including limited digital infrastructure in rural areas and low digital literacy among educators. This study highlights the importance of strategic interventions, including regulatory support, capacity-building programs, and infrastructure development, to ensure equitable access and sustainable implementation of digital technologies. The integration of digital technology not only streamlines administrative functions but also enriches interactive learning experiences and strengthens relationships between educators and learners.Effective digital transformation can serve as a catalyst for building more collaborative, transparent, and accountable faith-based education systems, while contributing to broader educational reform in Indonesia and similar contexts.